(untitled) (Педагогіка вищої та середньої школи, 2022)
The article analyses the experience of teaching of the academic discipline “Educational Technologies” in the higher educational establishments of Ukraine, its role in the formation of the professionalism of future teachers. This article suggests the possible structure of the course. Also the necessity of the connection of learning educational technologies andformation o f the individual pedagogical skills is proved.